Using Crossword Puzzles to Improve the Eighth Grade Students' Vocabulary Mastery - Prasetyo, Bagus; Fardhani, Aan Erlyana; Ariyanto, Sugeng (EFL Education Journal, 2016)
This article is intended to describe the result of the research onimproving students’ vocabulary mastery by using crossword puzzles. The research design was Classroom Action Research. The research subject and area of the research, the students of class VIII-G at SMPN 1 Bangsalsari Jember were determined by using purposive method. The research data collection methods werevocabulary mastery test, observation, interview, and documentation. The collected data were analyzed by using percentage formula. The result of observations showedthat the students were categorized active students and it increased up to 79% in Cycle 2. Further, the result of vocabulary mastery test indicated that the students achieved the standard minimum score in Cycle 2. Therefore, using crossword puzzles could improve the VIII-G students' vocabulary mastery and their active participation.